syl1
8

# (x-7)-2(3x+5)=3 2t-(3t-1)=6 3x+6=-2x+4 -7(x-2)=3x-1 5x+2=7-3x 3(2x-5=1-4x 4(x-6)-3x=2(x-9) 4(x-1)=6(1+x) 2(x+3)-5=-2x-7 -x+3=-(3x-2) 3(x+1)-(x+10)=x 2(3=2x)-3=3(x-1)-1

(1) Odpowiedź
renatkaaaa2

1. (x-7)-2(3x+5)=3 (x-7) - (6x+10)=3 x-7-6x-10=3 x-6x=3+17 -5x=20/ : (-5) x= - 4   2. 2t-(3t-1)=6 2t - 3t + 1 = 6 - t = 5 /: (-1) t = -5   3. 3x+6=-2x+4 3x + 2x = 4 - 6 5x = - 2 / : 5 x= - 2/5   4. -7(x-2)=3x-1 - 7x + 14 = 3x -1 - 7x - 3 x = -1 - 14 - 10 x = - 15  / : (-10) x = 15/ 10 x = 1,5   5. 5x+2=7-3x 5x + 3x = 7 - 2 8x = 5    /: 8 x= 5/8   6. 3(2x-5)=1-4x 6x - 15 = 1 - 4x 6x + 4 x = 1 + 15 10x = 16     /: 10 x=1 ⅗   7. 4(x-6)-3x=2(x-9) 4x - 24 - 3x = 2x - 18 x - 2 x = -18 + 24 - x = 6 /:(-1) x= - 6   8. 4(x-1)=6(1+x) 4x - 4 = 6+ 6x 4x - 6x = 6 + 4 - 2 x = 10   / :(-2) x=  - 5   9. 2(x+3)-5=-2x-7 2x + 6 - 5 = -2x - 7 4x = -7 -6 +5 4x= -8   /:4 x= - 2   10. -x+3=-(3x-2) -x + 3 = - 3x + 2 -x + 3x = 2 - 3 2x = - 1    /:2 x=  -½   11. 3(x+1)-(x+10)=x 3x + 3 - x -10 =x 2x - x = 10-3 x=7   12. 2(3-2x)-3=3(x-1)-1 6 - 4x - 3 = 3x -3 -1 -4x -3x =-3-1+3-6 -7x = - 7      / :(-7) x= 1

Dodaj swoją odpowiedź